Moderation of tax attitudes on the relationship of knowledge and tax incentives on sustainable MSMEs performance - Sari, Diana; Johan, Ahmad (Jurnal Akuntansi dan Auditing Indonesia, 2024)
Recently, public opinion regarding tax avoidance has become unbreakable; and issues related to tax institutions are disrupting tax revenues. Tax avoidance leads to an issue that still requires resolution and is firmly entrenched among the business community in developed countries. The small and medium business sector refers to a sector that is involved in aggressive tax avoidance practices. Thus, tax can be accepted as a problem to achieve sustainability. This research applies a fiscal psychology theory approach with a survey approach on 150 MSME owners in Bandung City, West Java. The collected data was then analyzed using the Partial least squares approach to test and analyze the hypothesis. The results of this research show that tax knowledge and the tax incentives provided have a positive effect on the sustainable business performance of MSMEs in Bandung. Apart from that, this research also proves that tax attitudes are a determinant that can strengthen or weaken the relationship between tax knowledge and the tax incentives provided in achieving sustainable MSME business performance. It is hoped that the results of this research will add to the literature and expand the body of knowledge, especially in the context of taxation and business performance, and for practitioners, especially business owners. It can be a consideration that compliance in paying taxes is an essential factor in achieving business performance.